Clinical and radiographic changes of carpi, tarsi and interphalangeal joints of beef zebu bulls on semen collection regimen - Motta, G. A. [UNESP]; Girardi, A. M. [UNESP]; Sabes, A. F. [UNESP]; Portugal, E. S.; Nociti, R. P. [UNESP]; Bueno, G. M. [UNESP]; Marques, L. C. [UNESP] (FapUNIFESP (SciELO), 2017)
Osteoarthritis and osteochondrosis are highly correlated to reproductive failure in bulls. This study aimed to evaluate the carpal, tarsal and interphalangeal lesions in beef zebu bulls on semen collection regimen. Twenty-one beef cattle bulls, in a total of forty-one animals, were split into three age-based groups: animals from two to four years old (GI), from more than four to eight years old (GII) and above eight years old (GIII). The clinical findings were conformational changes of limbs, synovial effusion, peripheral venous engorgement of joints and prolonged decubitus. The total population showed moderate clinical manifestation and radiographic score. The GIII presented more severe joint lesions. Carpi and tarsi regions had discrete to difuse osteophytosis, subchondral cysts, cartilaginous flaps, bone incongruence and fragmentation, osteitis, and ankylosis. Interphalangeal joints presented osteophytosis, distal phalanx osteitis and enthesophytosis. The digital radiographic examination allowed full identification of articular lesions and their clinical correspondences, besides the positive correlation between age, body weight and radiographic score.
Keywords: Cattle; Infertility; Male; Overweight; Radiology